Atlas of the forest sector in Northwest Russia 2009 - Gerasimov, Yuri; Karvinen, Sari; Leinonen, Timo (Finnish Forest Research Institute, 2009)
This atlas is a collection of maps with a short description of the current situation of the forest sector in Northwest Russia including regions of Karelia, Komi, Arkhangelsk, Vologda, Leningrad, Pskov, Novgorod, and Murmansk. The cartographic information is grouped in the following way: forest resources, silviculture, wood harvesting, production and the most important producers of wood-based products (sawnwood, plywood, wood-based panels, pulp, paper, paperboard), utilization of birch and aspen, as well as producers of forest-related machinery, wood pellets, and brickets. This review serves the information needs of different stakeholders and those interested in the forest sector in Russia. This atlas is a collection of maps with a short description of the current situation of the forest sector in Northwest Russia including regions of Karelia, Komi, Arkhangelsk, Vologda, Leningrad, Pskov, Novgorod, and Murmansk. The cartographic information is grouped in the following way: forest resources, silviculture, wood harvesting, production and the most important producers of wood-based products (sawnwood, plywood, wood-based panels, pulp, paper, paperboard), utilization of birch and aspen, as well as producers of forest-related machinery, wood pellets, and brickets. This review serves the information needs of different stakeholders and those interested in the forest sector in Russia. This atlas is a collection of maps with a short description of the current situation of the forest sector in Northwest Russia including regions of Karelia, Komi, Arkhangelsk, Vologda, Leningrad, Pskov, Novgorod, and Murmansk. The cartographic information is grouped in the following way: forest resources, silviculture, wood harvesting, production and the most important producers of wood-based products (sawnwood, plywood, wood-based panels, pulp, paper, paperboard), utilization of birch and aspen, as well as producers of forest-related machinery, wood pellets, and brickets. This review serves the information needs of different stakeholders ...